2004
DOI: 10.1111/j.1048-891x.2004.14610.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of CD10 antigen in uterine adenosarcoma

Abstract: Uterine adenosarcoma (UAS) is microscopically characterized by a biphasic growth pattern. By definition, the epithelial component is benign, whereas the stromal component typically has the appearance of a low-grade sarcoma, usually an endometrial stromal sarcoma. CD10 acts by reducing cellular response to peptide hormones and is currently regarded as a specific marker for endometrial stromal tumors. In this international multicenter study, we further explored CD10 immunoreactivity in 30 UASs. We encountered CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Even though desmin and SMA are usually expressed in ULMS, they have also been reported to be positive in 10–40% of ESS cases 28. Furthermore, positivity for CD10 ranged from 75% to 100% of ESS cases and from 0% to 60% of ULMS cases 15 19 29. Finally, even though h-caldesmon is very specific for ULMS, its Sen is only 50% 23.…”
Section: Discussionmentioning
confidence: 99%
“…Even though desmin and SMA are usually expressed in ULMS, they have also been reported to be positive in 10–40% of ESS cases 28. Furthermore, positivity for CD10 ranged from 75% to 100% of ESS cases and from 0% to 60% of ULMS cases 15 19 29. Finally, even though h-caldesmon is very specific for ULMS, its Sen is only 50% 23.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial description [1], hundreds of uterine and extra-uterine MAs have been reported in the literature [2,3,6,11,12,29,30], and although many studies focused on immunohistochemical profiles in attempts to distinguish MA from other uterine tumours and to aid with prognostication [8,9,11,12,31], no sensitive or specific diagnostic or prognostic marker has been identified to date. In the present study of 18 MAs, we have performed next-generation sequencing of a large panel of well-established oncogenes and tumour suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…and ER expression [8][9][10][11][12]. Some studies have found that p53 is aberrantly overexpressed in a few MAs with SO [11,15,16].…”
Section: Be Howitt Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 IMMUNOHISTOCHEMISTRY In most adenosarcomas with a low-grade stromal component, the stromal element expresses estrogen receptor, progesterone receptor, CD10, and WT1 and is negative for P53, which is similar to the immunophenotype of ESSs. 3,15,16 The CD10 is the common acute lymphoblastic leukemia antigen and is a membrane glycoprotein that functions as a cell surface enzyme, which reduces cellular response to peptide hormones, and is a specific marker for ESSs, which is commonly the stromal component in adenosarcomas. 16 Amant et al 16 reported that 90% (18/20) of uterine adenosarcomas were CD10 positive, whereas 63% (5/8) adenosarcomas with sarcomatous overgrowth were CD10 positive.…”
Section: Microscopicmentioning
confidence: 99%